Efektivitas kepemimpinan yang melayani dalam meningkatkan perilaku kerja inovatif: Sebuah seni dari keterlibatan kerja - Limbong, Lisnawati; Saragih, Susanti (Universitas Kristen Maranatha, 2023)
The purpose of this research is to examine the connection between servant leadership and innovative work behavior, with job engagement acting as a mediator. The study involved 211 high school and vocational schoolteachers in Bandung and utilized an online survey. Data analysis was performed using SmartPLS 3.2.9 for Windows. The findings confirm that servant leadership has a positive impact on innovative work behavior directly and that job engagement significantly mediates the relationship between servant leadership and innovative work behavior. This study is significant as research on the topic of servant leadership and innovative work behavior in a school context is relatively new. Due to the specificity of the set population within the school institution, the mechanism of how servant leadership impacts innovative work behavior could be better understood. These findings can assist schools’ management in developing innovative work behaviors and creating competitive advantages by creating a psychological connection.